Biomechanical properties of female dolphin reproductive tissue. (1st March 2019) - Orbach, D.N.; Rattan, S.; Hogan, M.; Crosby, A.J.; Brennan, P.L.R.
Graphical abstract: Abstract: Whales, dolphins, and porpoises have unusual vaginal folds of unknown function(s) that are hypothesized to play an important role in sexual selection. The potential function of vaginal folds was assessed by testing the mechanical properties of common bottlenose dolphin ( Tursiops truncatus ) reproductive tract tissues in 6 different regions and across age classes in post-mortem specimens. We assessed the regional (local) and overall effective elastic modulus of tissues using indentation and tensile tests, respectively. We explore the non-linear mechanical response of biological tissues, which are not often quantified. Indentation tests demonstrated that sexual maturity state, tissue region, force history, and force magnitude values significantly affected the measured effective elastic modulus. Tissue was stiffest in the vaginal fold region and overall stiffer in sexually immature compared to mature animals, likely reflecting biomechanical adaptations associated with copulation and parturition. Tensile tests showed that only tissue region significantly affected the effective modulus. Our data support the hypothesis that vaginal folds function as mechanical barriers to the penis and may provide females with mechanisms to reduce copulatory forces on other reproductive tissue. Statement of Significance: Cetaceans have unusual folds of vaginal wall tissue that appear to evolve under sexual selection mechanisms and present physical barriers to the penis during copulation. We explore the biomaterial properties of vaginal fold tissue, how it varies from other reproductive tract tissues, and ontogenetic patterns. We demonstrate that vaginal folds can withstand higher mechanical forces and respond in a manner conducive to dissipating copulatory forces to other reproductive tissues. This study yields exciting insights on how female genital tissue may function during copulation, and is the first to do so in any vertebrate species. Additionally, we provide an example for testing biological tissues, non-linear properties, and materials with uneven surface structure and uneven thickness.